The quality of maintenance works perform by maintenance contractor in Putrajaya / Muhammad Amirul Haziq Ratuah - Ratuah, Muhammad Amirul Haziq (Faculty of Architecture, Planning and Surveying, 2013)
Putrajaya is the federal government's administrative, and equipped by world class infrastructures. Thus the maintenance works that need to be taken at there must be according to designated regulation, so that it will remain the quote as federal government's administrative. The contractors need to be in a full knowledge and skills about maintaining the building, so that the building will remain in its own class. This study is to identify the quality of maintenance works that were performs by maintenance contractor at Putrajaya. The objective of this research is to study the maintenance management concept and practice that performs by maintenance contractor in Putrajaya, to determine the factor that influenced the quality of maintenance management, and to give a recommendation and proper suggestion on maintenance practice. From the data that has been collected, ail the information was arranged and analyse by using two methods, which are comparative method and questionnaire analysis. Comparative method is the method for comparing two case studies with all the information that have been collected. And questionnaire analysis is analyzing the data from set of questionnaire that have distributed at both case studies, through bar chart and pie chart. The quality and effectiveness of maintenance management can be seen by relating the condition of the building by occupant's view and the services given by maintenance worker. In that sense, the hypothesis of this study is "the better the performance by maintenance management, the better the condition of the building'. This study had found that lack of policy, mission and vision awareness among the employees can highly influence the performance of the company. Hence the implementation of good policy is necessary in determining the good performance of maintenance management.